Pemanfaatan jus apel (Malus sylvestri mill) dibandingkan jus jambu biji (Spidium guajava linn) dalam menurunkan halitosis pada remaja - Ratna Wilis; Andriani Andriani (Politeknik Kesehatan Kemenkes Aceh, 2019)
Background: Halitosis is caused by rotting food scraps by poor oral hygiene, and this condition can be exacerbated by irregular teeth composition. In this situation, the unpleasant odor can be reduced or eliminated by brushing teeth, using mouthwash and traditional methods by gargling / consuming fibrous fruits such as apples and guava. Riskesdas 2013, in general, people brush their teeth every day in the morning and evening bathing as much as 90.7% and before bedtime only 20.7%. The results of the examination on 20 oral hygiene students in the category of dental and oral hygiene were poor (60%). Measurement of halitosis manually by licking a spoon, then within 10 seconds is kissed manually if the odor caused is so stinging it belongs to the category of halitosis.Objective: to determine the effectiveness of consuming guava juice compared to apple juice on changes in the decrease in halitosis. The sample of 120 first grade students of SMPN 7 Banda Aceh was divided into 2 groups. The study was conducted on July 24 until August 1.Method: This research is quasi-experimental. Data analysis was tested using Paired t-test. Meanwhile, to find out the effectiveness of both of them is tested by the Independent Test t-test with a significance level of 95%.Results: The results showed that before consuming apple juice, the first measurement was 3.00 and the second was 3.02, after being given halitosis apple juice, the first mean was decreased by 1.70 and the second measurement was 1.58. Before consuming red guava juice, the average measurement was 2.98 and after giving red guava juice, it decreased to 2.22 (first measurement) and 2.13 (second measurement).Conclusion: The significant decrease in halitosis scores that consume apple juice has a better effectiveness in reducing the halitosis score compared to consuming red guava juice obtained p = 0,000.It is recommended: in schools to be able to consume apples and red guava fruit as natural ingredients to reduce bad breath or prevent bad breath (halitosis).